2020
DOI: 10.1002/jbm.b.34758
|View full text |Cite
|
Sign up to set email alerts
|

Physico‐chemical characterization and tissue healing changes byHancornia speciosaGomes latex biomembrane

Abstract: Skin wounds have been a public health concern of high frequency, in addition to requiring intensive and expensive care. The natural rubber latex (NRL) from Hancornia speciosa Gomes has been used to treat many problems in traditional medicine and also present healing properties, antifungal and anti‐inflammatory activity and antinociceptive effects. The purpose of this study was to characterize the new biomembrane from the NRL of H. speciosa (HS) by Fourier transform infrared (FTIR) and mechanical strength test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…Our findings are potentially applicable in repurposing opportunities for treating inflammation and promoting wound healing. The present in vitro study would be helpful in preclinical models for wound healing studies (Caetano et al 2015 ; Pegorin et al 2021 ). Further understanding of physiological C1q binding to DDR2 is necessary for therapeutic applications in wound healing-related diseases.…”
Section: Discussionmentioning
confidence: 97%
“…Our findings are potentially applicable in repurposing opportunities for treating inflammation and promoting wound healing. The present in vitro study would be helpful in preclinical models for wound healing studies (Caetano et al 2015 ; Pegorin et al 2021 ). Further understanding of physiological C1q binding to DDR2 is necessary for therapeutic applications in wound healing-related diseases.…”
Section: Discussionmentioning
confidence: 97%
“…The values of the elasticity modulus were close to those of human skin, in addition, cell biocompatibility and non-toxic characteristic were found, concluding that it is a safe and biocompatible biomaterial for the wound healing process due to its ability to stimulate inflammatory cells and initial angiogenesis. In addition, the study in an animal model showed an increase in collagenesis and an improvement in the quality of the healing process, suggesting that it is a good alternative to existing materials with the same function (PEGORIN et al, 2021).…”
Section: Dermo Protective Action -Woundsmentioning
confidence: 91%
“…Reports have also suggested a latex activity in bone regeneration, in promoting angiogenesis, as an antiinflammatory, antimicrobial and antifungal agent (PEGORIN et al, 2021), which has led to new preclinical studies, still in progress, with the use of compounds from HS latex in vivo. (Fig.…”
Section: Latex Of "Mangabeira"mentioning
confidence: 99%
See 2 more Smart Citations